HUKUM MENGINVESTASIKAN ZAKAT DAN URGENSINYA SEBAGAI INSTRUMEN DISTRIBUSI KESEJAHTERAAN - Kholik, Jamaludin Acmad (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2016)
Zakat is a worship related to treasure which socially has important position in Islam. So far, zakat collected by zakat institution is only divided to mustahiq as consumption so that it is just exhausted. A new thought is needed to make zakat has a greater role in empowering Muslim economy. This article aims at digging a law of zakat investment and its role in increasing communities’ welfare, investigating maqashid (purposes) of zakat obligation. The data sources are books about zakat, written both classic and contemporary ulama (scholars). The data analysis used is qualitative descriptive. One of new thought that can be applied is by investing zakat treasure with the purpose that the zakat treasure continuously increases, and the benefit can be used by mustahiq. Therefore, the optimization of zakat obligation can be realized so that it has great implication in increasing Muslim communities’ welfare. Un-optimization of zakat obligation can causes high level of poverty and unemployment of Muslim community.Key words; Investment, zakat, optimalization maqa>s}id, welfare